Implementasi Kebijakan Pendidikan Agama di Sekolah: Studi Terhadap Efektivitas dan Tantangan di Lapangan - Sakban Sakban; Carina Septiani; Sri Mulyani; Nur Azmi; Aida Efendy; Muthia Azzahra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Religious education plays a crucial role in shaping students' character and instilling moral and spiritual values. This study aims to analyze the implementation of religious education policies in schools, focusing on the effectiveness of implementation, challenges faced by teachers and institutions, and its impact on students. The research employed a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings indicate that although religious education policies are formally included in the curriculum, their implementation in practice still faces several obstacles, such as limited resources, lack of teacher training, and diverse religious backgrounds of students. Recommendations include improving teacher training, strengthening the curriculum, and adopting an inclusive approach that respects religious diversity.